2015
DOI: 10.1016/j.jastp.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the 15 January 2010 annular solar eclipse on the equatorial and low latitude ionosphere over the Indian region

Abstract: a b s t r a c tThe annular solar eclipse of 15 January 2010 over southern India was studied with a multi-instrument network consisting of magnetometer, ionosonde and GPS receivers. The presence of a counter electrojet (weakened or westward zonal electric field) during the eclipse and adjacent days suggests the strong gravitational tidal effect associated with the exceptional Sun-Moon-Earth alignment around the eclipse day. With a strong backup of magnetometer recordings on the day of eclipse, its adjacent days… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Such equatorial fountain disruption can happen if a strong westward electric field develops at the geomagnetic equator, which might be a realistic possibility considering a number of past solar eclipse studies that have reported cases of counter‐electrojet current when the eclipse totality trajectory traversed over the geomagnetic equator (e.g. Cheng et al, ; Panda et al, ; St.‐Maurice et al, ; Tomas et al, , ; Vyas & Sunda, ). The presence of westward electric field along the wake of the eclipse totality would also be consistent with the downward ionospheric drift velocity observed on 9 March 2016 over Guam during the last half of the solar eclipse (cf.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Such equatorial fountain disruption can happen if a strong westward electric field develops at the geomagnetic equator, which might be a realistic possibility considering a number of past solar eclipse studies that have reported cases of counter‐electrojet current when the eclipse totality trajectory traversed over the geomagnetic equator (e.g. Cheng et al, ; Panda et al, ; St.‐Maurice et al, ; Tomas et al, , ; Vyas & Sunda, ). The presence of westward electric field along the wake of the eclipse totality would also be consistent with the downward ionospheric drift velocity observed on 9 March 2016 over Guam during the last half of the solar eclipse (cf.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…The proxy equatorial electrojet (EEJ) strength to the EEJ current in the ionospheric E-layer was calculated by subtracting the local midnight baseline values from the magnetometer H variation at equatorial TIR and the off-equatorial ABG observatory, and then finding the difference between them, as shown in Equation (1). This approach was previously proposed by Nair et al [53], and thereafter used by many researchers as a proxy to understand the characteristics of transmitted fields and the state of the equatorial ionosphere, especially during the daytime [2,54,55].…”
Section: Local Magnetometer Data Processingmentioning
confidence: 99%
“…Several studies have indicated that an eclipse could induce rapid motion of low-pressure systems and cause significant wind convergence, triggering a local neutral wind dynamo that flows in a direction opposite to the normal daytime solar quiet (SQ) current system, and this feature has been termed a counter-SQ current pattern (Choudhary et al, 2011;St.-Maurice et al, 2011). Under these conditions, when the low-pressure system center (maximum obscuration) approaches the magnetic equator, the equatorial electrojet (EEJ) will be largely weakened and sometimes even a full-blown counter electrojet (CEJ) could be developed after the pass of maximum obscuration, a signature that fundamentally depends on competition between local and global dynamos (Cheng et al, 1992;Panda et al, 2015;Tomás et al, 2007Tomás et al, , 2008Vyas & Sunda, 2012). In the December 2019 eclipse event under study, the annular eclipse center crossed the magnetic equator in the early morning over Indian sector (see Figure 8a).…”
Section: Equatorial Local Time Eclipse Response and Counterelectrojetmentioning
confidence: 99%